Instruction to the authors of the Journal of Family and Community Medicine - Editor RBMFC (Sociedade Brasileira de Medicina de Família e Comunidade, 2007)
The Journal of Family Medicine and Community RBMFC) is a quarterly publication of the Brazilian Society of Family Medicine and Community, which aims to: raise awareness among professionals and health authorities in the area of interest of Family Medicine and Community; stimulate and disseminate research on issues and Primary Health Care (PHC), enabling the exchange between academia, service and social movement organizations, to promote the dissemination of abordageminterdisciplinar and serve as a vehicle for continuous and permanent education in the field of Family Medicine and Community taking as its theme the APS. Entries will be judged by the editors of Scientific and Editorial Board, as well as by invited peer ad hoc. The peer review process preserves the identity of the authors and their affiliations, which are reported to the Editorial Board only in the final stage of evaluation. All papers must be written in Portuguese, with the exception of written by foreign authors not resident in Brazil who can do it in English or Spanish